(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
carrot (Daucus carota subsp. sativus) is root vegetation that available in diversity of colors, comprising purple, black, red, white, & yellow. Carrots include carotenids, flavonoid, polyacetylens, vitamins, & minerals, all which provide diversity of nutritional health advantages. Carotenoids, polyphenols, & vitamins found in carrots function as antioxidants, anticarcinogens, & immune enhancers, proving ancient saying that carrots are excellent for eyes. Carrot has shown to have anti diabetic, cholesterol & cardiac disease reducing, anti hypertensive, hepatoprotective,renoprotective,&woundhealingproperties. Carrotseedextractshavecardio-hepatoprotective,antibacteral, antifungal, anti inflammatory, & analgesic properties. All of se topics are covered in this review essay. Carrots are important tuber crop that is high in biochemical elements like carotenoid and soluble fiber, as well as variety of other functional elements with wellness properties.. Carrot consumption is gradually rising as a result of its recognized as a valuable source of natural antioxidants with anticancer properties. Apart from being utilized in salads & curries in India, carrot roots may be professionally processed into nutritionally rich processed goods like as juice, concentrate, dry powder, tinned, preserve, c&y, pickle, & gazrailla. Carrot pomace, which contains approximately 50% -carotene, may be used to enhance goods such as cake, bread, & biscuits, as well as to make a diversity of useful products. nutritional content, health-promoting phytonutrients, functional characteristics, product creation, & by-products usage of carrot & carrot pomace, as well as ir prospective application, are all highlighted in this study.